Cretaceous magmatism in the Antarctic Peninsula and its tectonic implications - Bastias Silva, Miguel Joaquin; Spikings, Richard Alan; Riley, Teal; Chew, David; Grunow, Anne; Ulianov, Alexey; Chiaradia, Massimo; Burton-Johnson, Alex (Journal of the Geological Society, 2022)
Periods of cessation, resumption and enhanced arc activity are recorded in the Cretaceous igneous rocks of the Antarctic Peninsula. We present new geochronological (laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) zircon U–Pb) analyses of 36 intrusive and volcanic Cretaceous rocks, along with LA-ICP-MS apatite U–Pb analyses (a medium-temperature thermochronometer) of 28 Triassic–Cretaceous igneous rocks of the Antarctic Peninsula. These are complemented by new zircon Hf isotope data along with whole-rock geochemistry and isotope (Nd, Sr and Pb) data. Our results indicate that the Cretaceous igneous rocks of the Antarctic Peninsula have geochemical signatures consistent with a continental arc setting and were formed during the interval c. 140–79 Ma, whereas the main peak of magmatism occurred during c. 118–110 Ma. Trends in ε Hf t (zircon) combined with elevated heat flow that remagnetized rocks and reset apatite U–Pb ages suggest that Cretaceous magmatism formed within a prevailing extensional setting that was punctuated by periods of compression. A noteworthy compressive period probably occurred during c. 147–128 Ma, triggered by the westward migration of South America during opening of the South Atlantic Ocean. Cretaceous arc rocks that crystallized during c. 140–100 Ma define a belt that extends from southeastern Palmer Land to the west coast of Graham Land. This geographical distribution could be explained by (1) a flat slab with east-dipping subduction of the Phoenix Plate, or (2) west-dipping subduction of the lithosphere of the Weddell Sea, or (3) an allochthonous origin for the rocks of Alexander Island. A better understanding of the geological history of the pre-Cretaceous rocks of Alexander Island and the inaccessible area of the southern Weddell Sea is required. Supplementary material: A description of the methods used in this study and the complete dataset are available at https://doi.org/10.6084/m9.figshare.c.6089274